Factors influencing tax compliance and e-filing usage in Delhi ncr: An empirical analysis - Riyaz ali, Dinesh tandon (Journal of Informatics Education and Research, 2025)
The adoption and perceived usefulness of e-filing systems are the main topics of this study, which explores the variables affecting individual taxpayers' views and compliance behavior in india. The study examines how taxpayers' views and actions are impacted by tax knowledge, government spending, tax justice, perceived consequences of non-compliance, and the simplicity of e-filing through the use of structural equation modeling (sem) and a robust research methodology (rm). The results show that tax expertise has no discernible impact on the perceived utility of e-filing, suggesting that a greater comprehension of tax laws does not always translate into a higher value for the digital filing method. However, the perceived usefulness and usability of e-filing platforms are greatly increased by perceived online tax filing, considered tax justice, and perceived penalty of non-compliance. The perceived value of e-filing, on the other hand, is adversely affected by the perception of government spending, indicating that taxpayers' opinions regarding the effectiveness of government might erode confidence in digital systems. Additionally, increased tax compliance is a result of favorable perceptions of the tax system, which are influenced by the perceived value and simplicity of e-filing. By stressing the dangers of non-compliance, justice, and convenience of use, these studies give policymakers important insights to enhance digital tax systems. The study adds significant implications for improving taxpayer involvement and compliance to the body of knowledge on tax compliance and digital tax systems. Future studies should examine how cross-national comparisons, technological advancements, and demographic characteristics influence tax compliance behaviour.